BENTUK DAN RAGAM HIAS PADA NISAN MAKAM-MAKAM DI SITUS BENTENG LIPU KABUPATEN BUTON UTARA - Hekta Plantikano; Syahrun Syahrun; Salniwati Salniwati (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
The problem in this study is how the shape and decoration of gravestones with the aim to know and explain the shape of gravestones, as well as describing the various kinds of ornamentation that exist on the graves on the Benteng Lipu Site. The research method used is descriptive analytical which consists of several stages, namely the study of literature in the form of books, journals, theses, theses, articles and supplemented with observational data, interviews and documentation. The results showed the form of headstone consists of several types / shapes. The gravestone forms found at the Lipu Benteng Site were rectangular shapes, hexagon shapes, pyramid shapes, round shapes, flat shapes and irregular shapes. Aside from the gravestone forms, there were also decorative art identified in the grave graves at the Lipu Benteng Site, namely, geometric types and fauna types. Geometric type resembles were carving of a tumpal shape, the shape of horizontal lines medallion shape of an irregular circle, the shape of the mosque dome and the shape of the crown upside down. This type of fauna has a shape like sea shells.